Post-implant biocompatibility of electro-spunded polycapronolactone nanocomposite fibrous scaffolds - Missana, Liliana Raquel (2020)
Tissue engineering aims regenerating de novo lost tissue. Our objective was to analyze the biocompatibility of the implant of PCL-nHAp, an electro-spun scaffold prepared by mixtures of a biocompatible and bioabsorbable polyester, poly(caprolactone), and a bioactive ceramic of nanofibrous structure (nanohydroxyapatite particles), in an in vivo model (New Zealand female rabbits). Scaffolds were 5 mm diameter PCL-nHAp discs, superficially modified to increase hydrophilicity by alkaline treatment and sterilized (peracetic acid). Treatments were (I) control, no bone lesion, (II) metaphyseal femoral bone lesion 3 mm deep and 5 mm diameter and PCL-nHAp implant; (III) lesion but no implant (n=6). Rabbit?s clinical evolution was adequate, without affecting gait. No differences in biochemical values (hemograms and transaminases) were detected after 1; 5 and 90 days. Histological studies (90days, 4n) showed that PCL-nHAp scaffold with a corrugated appearance, surrounded, from the outside inwards: A-Hematopoietic bone marrow with megakaryocytes and / or fat with congestive areas; B- few incipiently formed trabeculae, of varied forms;and C- presence of multinucleated giant cells, macrophages, lymphocytes combined with areas of hemorrhage and congestion. An adequate biocompatibility of the scaffolds can be observed, which in its imminent degradation process has not affected the biochemical parameters studied. A non-toxic and biologically active histological response is observed, with moderate levels of inflammation. We believe that longer post-implant periods will allow definitive conclusions.